'The Cliffs are not Cliffs': The Cliffs of Dover and National Identities in Britain, c.1750–c.1950. Issue 335 (April 2014) - Readman, Paul
Abstract This article examines the relationship between landscape and British national identities by means of a case study of the white cliffs of Dover in Kent, England. The cliffs were important symbols of island‐nationhood across the modern period, and demonstrate that even in the age of empire British as well as English national identities could be conceptualized in distinctly insular ways. In particular, the cliffs were seen to be associated with the national homeland, its heritage and historical continuity over hundreds of years, as well as with national defence and a defiant self‐asserted separateness from the rest of Europe. The article has implications for the (still relatively neglected) role played by specific landscapes in the construction of national identities, not just in Britain but generally. In functioning as markers of national difference the physical distinctiveness of these landscapes was important, but their associational value mattered more.